Human capital development: the importance of constructing auditory processing intervention instrument for underachiever students - Abd Rahman, Fadzilah; Yahya, Nurul Aini (IEEE, 2009)
It is very seldom for us to think that in the communication process, the most important element is the listener (student) to be able to capture and process the information that we delivered to them accurately. Besides, have we ever think that even if the students are not considered as having learning disabilities, there are also students who might have the trouble to listen, understand and respond to the learning content that we delivered to them? Have we ever thought about how to measure, how far or how accurate that the students have achieved or responding back to us about what they have learned before? A study showed that the students that are having less listening ability are synonym with the problem of interaction, academic and behavior (Rowe, Stephanou & Hoad, 2007). If we let this kind of problems to continue, these students will have high potentials to drop outs. Moreover, this paper will also suggests the development of the auditory processing intervention instrument to identify the auditory processing abilities among students in higher education institution.